Kinematic sub-populations in bull spermatozoa: a comparison of classical and bayesian approaches - Víquez, Luis; Barquero, Vinicio; Sole, Carles; Roldan, Eduardo R.S.; Valverde, Anthony (Biology 2020, 2020)
The ejaculate is heterogenous and sperm sub-populations with different kinematic patterns can be identified in various species. Nevertheless, although these sub-populations are statistically well defined, the statistical differences are not always relevant. The aim of the present study was to characterize kinematic sub-populations in sperm from two bovine species, and diluted with different commercial extenders, and to determine the statistical relevance of sub-populations through Bayesian analysis. Semen from 10 bulls was evaluated after thawing. An ISAS®v1 computer-assisted sperm analysis (CASA)-Mot system was employed with an image acquisition rate of 50 Hz and ISAS®D4C20 counting chambers. Sub-populations of motile spermatozoa were characterized using multivariate procedures such as principal components (PCs) analysis and clustering methods (k-means model). Four different sperm sub-populations were identified from three PCs that involved progressiveness, velocity, and cell undulatory movement. The proportions of the different sperm sub-populations varied with the extender used and in the two species. Despite a statistical difference (p < 0.05) between extenders, the Bayesian analysis confirmed that only one of them (Triladyl®) presented relevant differences in kinematic patterns when compared with Tris-EY and OptiXcell®. Extenders differed in the proportion of sperm cells in each of the kinematic sub-populations. Similar patterns were identified in Bos taurus and Bos indicus. Bayesian results indicate that sub-populations SP1, SP2, and SP3 were different for PC criteria and these differences were relevant. For velocity, linearity, and progressiveness, the SP4 did not show a relevant difference regarding the other sperm sub-populations. The classical approach of clustering or sperm subpopulation thus may not have a direct biological meaning. Therefore, the biological relevance of sperm sub-populations needs to be reevaluated.
Artículo científico
Keywords: Cinemática; Motilidad; Fertilidad -- Ganado; Especies bovinas; Toro -- Fertilidad; Calidad del semen; Kinematics; Motility; Fertility--Cattle; Bovine species; Bull -- Fertility; Semen quality; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Animal production